2017
DOI: 10.3390/molecules22060885
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Targets of Resveratrol on Lymphoma and Leukemia Cells

Abstract: Resveratrol (RSV) is a well known chemopreventive molecule featuring anti-cancer properties. Our paper describes the main molecular targets of RSV linked to its antiproliferative activity on lymphoma and leukemia experimental models. It discusses further the most recent and most promising among these molecular targets for a translational application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 81 publications
0
13
0
Order By: Relevance
“…RSV has been shown to inhibit in vitro growth of several cancer cells, including human acute lymphocytic and non-lymphocytic leukemia cell lines such as HL-60 (promyelocytic leukemia) [2], K562 (chronic myelogenous leukemia) [3], and CEM-C7H2 (T-acute lymphocytic leukemia) [4]. Several mechanisms have been proposed for the growth inhibitory effect of RSV, including induction of leukemia cell differentiation, apoptosis, and cell cycle arrest at the S phase and inhibition of DNA synthesis by inhibiting ribonucleotide reductase or DNA polymerase [5].…”
Section: Introductionmentioning
confidence: 99%
“…RSV has been shown to inhibit in vitro growth of several cancer cells, including human acute lymphocytic and non-lymphocytic leukemia cell lines such as HL-60 (promyelocytic leukemia) [2], K562 (chronic myelogenous leukemia) [3], and CEM-C7H2 (T-acute lymphocytic leukemia) [4]. Several mechanisms have been proposed for the growth inhibitory effect of RSV, including induction of leukemia cell differentiation, apoptosis, and cell cycle arrest at the S phase and inhibition of DNA synthesis by inhibiting ribonucleotide reductase or DNA polymerase [5].…”
Section: Introductionmentioning
confidence: 99%
“…New and old cellular and tissue targets are characterized for resveratrol and derivatives. Ferraz da Costa et al [ 11 ], and Frazzi & Guardi review cellular and molecular targets of resveratrol on lymphoma and leukemia cells [ 12 ], and León et al review the implications of resveratrol on glucose uptake and metabolism [ 13 ]. Finally, Wahab et al [ 14 ] put forward the significance of resveratrol in clinical management of chronic diseases.…”
mentioning
confidence: 99%
“…These benefits have resulted in extensive research into finding new natural compounds and revealing their potential mechanisms of actions [ 15 , 16 , 17 ]. Resveratrol (Res) is a dietary phytochemical that has been reported to be efficacious treatment for various ailments by targeting diverse molecular pathways [ 18 , 19 , 20 , 21 ]. The role of Res in the treatment of chronic diseases was established in early 1990s when it was found that this phytochemical possesses significant cardioprotective benefits [ 22 ].…”
Section: Resveratrolmentioning
confidence: 99%